Biaxial experiments and numerical analysis on damage and fracture in anisotropic aluminium sheets - Brünig Michael; Koirala Sanjeev; Gerke Steffen (MATEC Web of Conferences)
The technical note deals with the effect of stress state and loading direction with respect to the principal axes of anisotropy on damage and failure behaviour of the anisotropic aluminium alloy EN AW-2017A. Experiments with biaxially loaded specimens and corresponding numerical simulations have been performed to develop a damage criterion and a damage rule predicting macroscopic damage strains. Digital image correlation is used to monitor evolution of strain fields whereas failure modes on fracture surfaces are visualized by scanning electron microscopy. In addition, numerical calculations on the micro-level considering void-containing representative volume elements reveal further information on microscopic damage and failure processes. Based on the experimental data and numerical results of three-dimensionally loaded unit-cells damage laws depending on the stress state and on the load direction are developed. They are validated by numerical simulation of the tests with biaxially loaded specimens showing good agreement of experimental and numerical results. It is detected that the stress state, the load ratio and the loading direction have an influence on the width and the orientation of localized strain fields as well as on the formation of damage processes and fracture modes on the micro-scale.